2015
DOI: 10.1093/intqhc/mzv059
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' preferences of care within hospitals: a systematic literature review

Abstract: Patient-rated importance was a useful method in identifying the care patients preferred. Due to a limited number of studies and great diversity within studies evaluated, interpretation of results should be cautious. However, it seems that cancer patients treated in hospitals with a curative intent find treatment-related information, professional standard and short delay of diagnosis and treatment most important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Consistent with international reviews, quality of care was important to both rural and urban participants (Petersen, Knudsen, & Vinter, 2015;Victoor et al, 2012). Despite this, this study suggests that although some patients sought information about potential providers through online or personal contacts, most relied on advice from their referring clinician regarding the quality of specialists or services referred to.…”
Section: Quality Of Care and Trustmentioning
confidence: 59%
“…Consistent with international reviews, quality of care was important to both rural and urban participants (Petersen, Knudsen, & Vinter, 2015;Victoor et al, 2012). Despite this, this study suggests that although some patients sought information about potential providers through online or personal contacts, most relied on advice from their referring clinician regarding the quality of specialists or services referred to.…”
Section: Quality Of Care and Trustmentioning
confidence: 59%
“…The item addressing the involvement of the family or a close person in the patient's care was also rated by some patients as being less relevant. However, we decided to retain this item because the feedback received by patients was not consistent across settings or countries, and because there is evidence from a larger study involving cancer patients from various cultural backgrounds that for the majority family members are involved in patient care (Hobbs et al., ; Petersen, Knudsen, & Vinter, ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be 1 reason for our institution's diagnosis to treatment time being quite long. Petersen and colleagues 14 showed that diagnosis to first treatment time has correlation with patients' satisfaction.…”
Section: Discussionmentioning
confidence: 99%